Feeding and reproductive behavior of the dung beetle Canthon rutilans cyanescens (Coleoptera: Scarabaeinae) - Medina Hernández,Malva Isabel (2020)
Abstract Canthon rutilans cyanescens is a telecoprid and coprophagous dung beetle subspecies that builds two types of balls with feeding and nesting purposes. This paperwork describes some behavior and development time characteristics, as well as it analyses the influence of the type and amount of food on this species feeding and reproductive behavior. Adult individuals were sampled in Atlantic Forest areas in southern Brazil (between 2014 and 2016) and they were kept in laboratory conditions within 24 and 27 °C in a 12 hours photoperiod. Development time was observed on brood balls built by 40 couples fed with domestic dog feces. The weight and number of brood and food balls produced by each couple were measured and counted in an experiment with 50 couples fed with feces from distinct mammal’s species as well as in another experiment with 28 couples fed with 1g and 5g of domestic dog feces, distributed into two groups: small and large body size couples. The subspecies’ behavior varied according to the quality of the food resource, with omnivore feces as the best one, possibly due to the higher nutritional quality and microorganism’s diversity. In addition, individuals’ size influenced parental investment and the availability of food resource affected dung beetle’s reproductive success, since, when less food was offered, smaller amounts of food balls and smaller brood balls were built by the adult couples. Our results demonstrated that Canthon rutilans cyanescens has a rapid development and a behavioral plasticity related to the quality and the amount of food.